Efektifitas Peran Guru Pada Deteksi Dini Suspect Flatfoot Di Sekolah Dasar Kecamatan Ngemplak - Alfan Zubaidi; Sri Surini Pudjiastuti (Poltekkes Kemenkes Surakarta, 2018)
Abstract : The role of teacher, Flatfoot, Dynamic Balance. Children are growing well of motoric and sensoric activities. Their activities always use of lowerlimbs (legs). A problem which often rise on foot is flat foot. The purpose of this research is to know the effectiveness of the role of teachers in early detection of suspect flatfoot. this study is quasi experiment, with one gruop pre and post test design, variable in this study consists of the role of teacher effectiveness and early detection of flatfoot. This study was conducted in SDN Giriroto I, SDN Sindon I, and SDN III Manggung. Subjec of this study 32 teacher and 32 students (ages 6 – 8 years). Instrument in this study are Foot print and stopwatch. Data analysis using linear Regression and T tests. There was the influence of the teacher's role by administering the intervention (p value 0.000 < 0.05). There is the influence of dynamic balance by administering the intervention (p value 0.000 < 0.05). Linear regression test results obtained niali ρ = 0.016 indicates that there is a significant influence on the effectiveness of the role of the teacher towards early detection of flat foot. The effectiveness of the role of teachers affected by the grant of training on early detection of flat foot.